2015
DOI: 10.1080/15226514.2015.1045130
|View full text |Cite
|
Sign up to set email alerts
|

Treating Urban Wastewater: Nutrient Removal by Using Immobilized Green Algae in Batch Cultures

Abstract: Essential roles of microalgae during the tertiary treatment of municipal wastewater have been proven. In order to avoid wash out of the biomass and also modify the quality of the treated wastewater; some techniques such as cell immobilization have been developed. To do so, in this study four samples from two species of microalgae (Chlorella vulgaris and Chlamydomonas sp.) were determined and confirmed by taxonomic identification. The samples were immobilized in calcium alginate beads. Within 10 days the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Comparing monocultures, some algal species are equally capable of removing N and P and of adapting to different wastewaters [27][28][29][30]. In other cases the proportion of N to P removed differs significantly between algal species treating a single wastewater [31][32][33], indicating appropriate species selection can promote nutrient removal. There are species dependent responses to environmental conditions [34; 35] which mean in an open system seasonal variations can cause fluctuations in the species present and remediation rates [36].…”
mentioning
confidence: 99%
“…Comparing monocultures, some algal species are equally capable of removing N and P and of adapting to different wastewaters [27][28][29][30]. In other cases the proportion of N to P removed differs significantly between algal species treating a single wastewater [31][32][33], indicating appropriate species selection can promote nutrient removal. There are species dependent responses to environmental conditions [34; 35] which mean in an open system seasonal variations can cause fluctuations in the species present and remediation rates [36].…”
mentioning
confidence: 99%
“…The presence of various forms of nitrogen and phosphorous in wastewater leads to eutrophication [38]. C. vulgaris has a high potential to reduce nutrients in secondary waste water treatment plants effluents [39] [40] [41] while simultaneously producing algal biomass with sufficient lipids content and an acceptable fatty acids profile for use as a biodiesel feedstock [42].…”
Section: Resultsmentioning
confidence: 99%
“…Many recent studies have reported the advantages of plankton culture under controlled conditions for attaining greater quality and quantity of biomass at lesser duration. Phytoplankton are potentially important for environmental impact assessment studies, synthesis of bioactive compounds, pigments, biofuels and applications in phytoremediation of contaminated wa-ter [3][4][5][6][7][8]. Most of the phytoplankton are sensitive to the ambient environmental conditions hence their community structure and biodiversity depends on ambient levels of nutrients, temperature, salinity, pH and light [9].…”
Section: Introductionmentioning
confidence: 99%